Electoral systems : a comparative introduction - Farrell, David M., 1960- (Houndmills, Basingstoke, Hampshire, UK ; New York : Palgrave Macmillan, 2011)
"Electoral Systems examines the six principle types of electoral system currently in use in more than seventy of the world's democracies. A common format is adopted throughout, dealing with explanations of how the system operates and its effects on the political system."--
The study of electoral systems: -- Why study electoral systems? -- Classifying electoral systems -- Conflicting views on the meaning of 'Representation' -- Conclusion -- The single member plurality system and its cousins: -- The Single-Member Plurality system in practice -- Britain's long road to electoral reform -- The electoral reform debate in other SMP Countries -- Other plurality systems -- Conclusion -- Majority electoral systems : two-round systems and the alternative vote: -- The two-round system -- The alternative vote system -- Assessing majority electoral systems -- Conclusion -- The list systems of proportional representation: -- The origins of list PR Systems -- Electoral formulas: largest remainders and highest averages -- District magnitude : constituency size and multi-tier districting -- Ballot structure : closed, ordered and open lists -- The operation of the list PR System in the Netherlands -- Conclusion -- Mixed-member electoral systems: -- The operation of Germany's mixed-member electoral system -- Proportionality, parties and politics in Germany -- Other mixed-member electoral systems -- Conclusion -- The single transferable vote system of proportional representation: -- STV in Ireland -- How STV Works -- Variations in STV design -- The consequences of STV for the political system -- Conclusion -- The consequences of electoral systems: -- Proportionality profiles of different electoral systems -- Electoral systems and party systems -- Parliament as a 'Microcosm'? -- The strategic effects of electoral systems -- Conclusion -- The politics of electoral system design: -- The origins of electoral systems -- the reform of electoral systems -- Explaining the origins and reform of electoral systems -- Political scientists as electoral engineers -- Measuring voter attitudes towards electoral systems -- Conclusion -- Electoral systems and electoral institutions: -- Built-in Distortions to electoral systems -- Reform of election management -- Conclusion -- Electoral systems and stability: -- PR and Government stability and Accountability -- PR and the Rise of extremist parties -- System complexity, voter confusion and electoral behaviour -- Is there a trade-off between proportionality and stability? -- Conclusion.
Includes bibliographical references and index.
Keywords: Elections; Representative government and representation; Political Science -- Political Process -- Elections; Political Science -- Public Policy -- General; Political Science -- Government -- General; Elections; Representative government and representation